Rationale and design of a multicenter randomized study comparing the efficacy and safety of esaxerenone versus trichlormethiazide in patients with uncontrolled essential hypertension: EXCITE‐HT study - Kazuomi Kario; Mitsuru Ohishi; Tomohiro Katsuya; Takashi Taguchi; Ayumi Tanabe; Kotaro Sugimoto; Tatsuo Shimosawa (The Journal of Clinical Hypertension, 2023)
Abstract The next‐generation mineralocorticoid receptor blocker (MRB) esaxerenone has favorable antihypertensive effects in patients who do not respond to treatment with first‐line antihypertensive agents and may be beneficial as a second‐line treatment. However, MRBs are currently considered a fourth‐line treatment as there is no clinical evidence comparing the efficacy of esaxerenone with other classes of antihypertensive agents. The multicenter, randomized, open‐label, parallel‐group EXCITE‐HT study will evaluate the efficacy and safety of esaxerenone as a second‐line agent in the treatment of Japanese patients with uncontrolled essential hypertension. After a 4‐week run‐in period, patients will receive either esaxerenone or trichlormethiazide for 12 weeks per the package insert and the Japanese Society of Hypertension Guidelines for the Management of Hypertension. At Weeks 4 and 8, the dose of esaxerenone or trichlormethiazide may be increased. Blood pressure (home [morning and bedtime] and office), serum biomarkers, and urinary biomarkers will be measured. The primary efficacy endpoint is the change from baseline in morning home systolic blood pressure/diastolic blood pressure to the end of treatment. The EXCITE‐HT study is expected to validate the non‐inferiority of esaxerenone to trichlormethiazide and provide the first evidence for the early use of esaxerenone as a second‐line agent in the treatment of Japanese patients with uncontrolled essential hypertension instead of its current use as a fourth‐line agent.